EXPERIENCES OF PUBLIC SERVANTS FACING DEATH FROM COVID19 - NAVARRO-NAVARRO, Ysabel (2024)
An unexpected situation appeared in the world, a global health crisis, but also a social one. Death, then, went from being a sporadic or exceptional event to having a daily presence, as it occurred suddenly, surprising and massively, we refer to the COVID 19 pandemic.Indeed, the losses of close people due to COVID-19 occurred in a special and unexpected context, however, the services of the Ministry of Women and Vulnerable Populations (MIMP) continued to operate as they were in charge of problems of priority interest. Public. We consider important to know the experiences of its professionals who went through the death of family members and colleagues due to the pandemic, during the years 2020 and 2021.A preview of a larger qualitative study was carried out, the sample was made up of 5 professionals, to whom a semi-structured interview was conducted that collected information about the study categories. The results indicate that the MIMP staff went through a moment of confusion and fear, before the arrival of COVID19, however, the services in favor of vulnerable populations and women affected by violence continued to function, with a high level of commitment and response capacity in the face of an unprecedented situation; The most significant losses are related to family members, but deaths of colleagues who shared the moments of crisis and coping in the daily life of the public serviceare also reported. Finally, the need to implement accompaniment spaces, therapeutic support or alliances with entities, since it is important and urgent to preserve the mental health of their workers.